2006
DOI: 10.1093/jat/30.7.458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Cocaine Administration on Detection Times in Oral Fluid and Urine

Abstract: Detection times reported for single-dose studies may not predict detection times following repeated cocaine dosing. Although repeated cocaine administration can result in drug accumulation and extended excretion time, there is a paucity of data from controlled dosing studies with repeated drug administration. We compared detection times for cocaine and benzoylecgonine (BZE) in oral fluid and BZE in urine following single and repeated cocaine dosing. Two groups of cocaine-experienced subjects participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 8 publications
3
33
0
1
Order By: Relevance
“…Only a few investigators have evaluated the pharmacokinetics of orally administered cocaine and even less has been published about the pharmacokinetics of chronic cocaine administration [6,7,8]. These results do not match with previous data known about the rapid decrease of cocaine and acceptance that drugs in saliva follows the same metabolic course that in blood.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Only a few investigators have evaluated the pharmacokinetics of orally administered cocaine and even less has been published about the pharmacokinetics of chronic cocaine administration [6,7,8]. These results do not match with previous data known about the rapid decrease of cocaine and acceptance that drugs in saliva follows the same metabolic course that in blood.…”
Section: Discussionmentioning
confidence: 68%
“…These authors indicate an average life of elimination of cocaine in saliva between 21.6-110.4 h. In chronic users even it can reach 10 days with a LOD 0, 5 ng/ml. Other authors agree with this statement [7]. It remains unclear how repeated dosing alters or prolongs detection times.…”
Section: Discussionmentioning
confidence: 84%
“…A real practice study of 16 pregnant women on methadone therapy for opiate abuse involving 403 OF samples (13 ), with LOQs of 1 g/L, found COC 111 times compared to 98 times for BZE. Additional reports (10,11 ) showed that repeated dosing of COC in 6 male individuals led to prolonged detection times for COC and BZE in both OF and urine compared with detection times from single-dose experiments. Importantly, OF COC and BZE were shown to have different elimination profiles (10,11 ), COC having a rapid initial elimination phase followed by a much slower one, and OF BZE with only a single, intermediate one.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reports (10,11 ) showed that repeated dosing of COC in 6 male individuals led to prolonged detection times for COC and BZE in both OF and urine compared with detection times from single-dose experiments. Importantly, OF COC and BZE were shown to have different elimination profiles (10,11 ), COC having a rapid initial elimination phase followed by a much slower one, and OF BZE with only a single, intermediate one. These results were attributed to storage of COC in adipose tissue, resulting in prolonged release of COC during abstinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation